Immune checkpoints: A therapeutic target in triple negative breast cancer - Chawla, Akhil (Landes Bioscience, 2014)
Early clinical trials investigating monoclonal antibodies targeting the T-cell inhibitory receptor programmed cell death 1 (PD-1) and its ligand PD-L1 have shown efficacy in melanoma, non-small cell lung cancer and renal cell carcinoma. We recently demonstrated PD-L1 expression in 20% of triple negative breast cancers suggesting that targeting the PD-1/PD-L1 immune checkpoint may be an effective treatment modality in patients with this disease.